MXene and polyaniline coated 3D-printed carbon electrode for asymmetric supercapacitor - Mappoli, Shidhin; Ghosh, Kalyan; Pumera, Martin (TAYLOR & FRANCIS LTD, 2024)
3D printing has emerged as an attractive manufacturing technique in supercapacitor electrodes owing to the precise and customisable fabrication of complex electrode designs, enhancing the performance and efficiency of the device. Despite the advantages, 3D-printed electrodes are limited by their low conductivity and electrochemical properties, predominantly due to the lack of availability of suitable conductive materials. To address this limitation, we modified the 3D-printed nanocarbon (3D-PnC) electrode by activation and surface deposition of Ti3C2Tx MXene. A solid-state asymmetric supercapacitor was fabricated by using 3D-PnC/Ti3C2Tx as the negative electrode and polyaniline (PANI) electrodeposited 3D-printed nanocarbon electrode (3D-PnC@PANI) as the positive electrode. The fabricated symmetric supercapacitor exhibits enhancement in overall voltage window, areal capacitance and energy density. The successful operation of the supercapacitor was demonstrated by the illumination of the red light-emitting diodes. Furthermore, this research opens the possibility of utilising MXene-modified 3D-printed electrodes for various electrochemical applications and devices.
Keywords: Solid-state supercapacitors; energy storage; MXene; PANI; fused deposition modelling